ANALISIS STATIK PERBAIKAN STRUKTUR PELAT-BERPENGUAT MELALUI PERHITUNGAN NUMERIK DAN PENGUJIAN - Hidayat, Wahyu
Abstract: Aircraft structural repair is very important to keep the aircraft airworthy. Negligance in performing the repair can cause fatal accident. Aircraft manufacturers provides a Structural Repair Manual (SRM) for each aircraft type for the user of the aircraft so that repair work can be performed properly. The SRM contains detailed procedures to conduct the repair. Aircraft structures consist of largely of thin sheets stiffened by different shape of stringer. A finite element analysis is performed for a stiffened sheet with simulated flaw on the stringer. A repair scheme for such a damage in the SRM of CN-235 aircraft is adopted in the analysis. Load transfer analysis of the rivets shows that the maximum load close to the simulated damage is reduced by the repair patch. Experimental results shows difference with analysis depending on the model of the rivet. The difference might be due to secondary bending moment, not accounted in analysis.